Sistem Pemerintahan Islam Perspektif Muhammad Rasyid Ridha dan Ali Abdurraziq - Rani, Hanifah Maha; Yazwardi, Yazwardi; Mikail, Kiki (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The development of Islamic political thought has been going on for 15 centuries and Islam is a distinctive and independent cultural unit. Political Thought examines the exercise of power, who deserves to exercise it and how much power they can have. Political Thought tries to explain the concept of Justice that is carried out in human relations, especially in the system of government between the ruling and the ruled, including the thoughts of Islamic leaders who have their own views regarding the Islamic government system. The purpose of this study was to determine the Islamic government system according to Muhammad Rasyid Rida and Ali Abdurraziq. This research is a library research. Data collection was obtained from library materials such as scientific books, journal articles, encyclopedias and other written sources, both printed and electronic. To analyze this research, in analyzing the data, the writer uses descriptive technique. Based on the results of the research data, it can be concluded as follows. That they are reformers who are in the contemporary period such as Rasyid Rida, an Islamic political thinker as well as a politician of the Muslim Brotherhood who defends a type of government characterized by popular sovereignty, namely a government formed by representatives and deliberation through ahlul halli wa al aqdi because Rasyid Ridha has a view regarding the Islamic government system. where the Caliphate is needed which of course its function is to fulfill worldly interests and regulate the religious affairs of the Muslims. Meanwhile, the thought of Ali Abdurraziq who is also an Islamic political thinker who once worked as a judge of the Syar'iyah Court is that the caliphate is an outmoded Islamic political institution and only causes disasters for Muslims. The Islamic political institution only existed at the time of the Prophet in its perfect form.